THE TUNA LiVfi-BAlT FISHERY OF MINICOY ISLAND - Jones, S (Indian Journal of Fisheries, 2016)
Specimens of fishes of Minicoy Island including tuna live-bait fisheswere being collected for the last four years through the co-operation of theMedical Officers stationed there. In October 1956, Mr. M. Kumaran,Laboratory Attender of this Research Station, was sent there to collectspecimens of fishes and information on the fishing industry. In February1958 I was able to visit the Island on board the Research Vessel ' Kalava'of the Indo-Norwegian Project and personally see the tuna bait fishery andcheck the information collected.